Alternative Fueling Scheme for the Indonesian Experimental Power Reactor (10 MWth Pebble-Bed HTGR). (December 2017) - Liem, Peng Hong; Tran, Hoai-Nam; Sembiring, Tagor Malem; Arbie, Bakri; Subki, Iyos
Abstract: The National Nuclear Energy Agency of Indonesia (BATAN) is launching a plan (2014) to build an 10 MWth Experimental Power Reactor ( Reaktor Daya Eksperimental, RDE) in the Agency's largest Research Center site, i.e. the Puspiptek Complex, Serpong, South Tangerang, Banten, as a first strategic milestone for the introduction of large scale nuclear power plant fleets into the country. The main objective of the plan is to demonstrate safe and reliable electricity and process heat generation from a nuclear reactor. The RDE is a very small sized pebble-bed high temperature gas-cooled reactor (HTGR) with low enriched uranium (LEU) UO2 TRISO fuel. Following our previous design study with multipass fueling scheme, a scoping study on fuel composition parameters, namely heavy metal (HM) loading per pebble and uranium enrichment was conducted for the simpler once-through-then-out (OTTO) fueling scheme. No need of burnup measurement devices and refueling mechanism to send back discharged fuel pebbles into the core, low power and power density, and simple operation of the RDE become strongest motivation for the present work. The objective function for the optimization is the fissile loading requirement per energy generated (kg/GWd). The optimal heavy metal loading was found around 8 g/pebble while the uranium enrichment corresponding to the 80 GWd/t discharge burnup constraint is approximately 13.7 w/o. Compared with the burnup calculations results of multipass fueling scheme, OTTO fueling scheme burnup performance is slightly inferior in that slightly higher enrichment and fissile loading per pebble are required to achieved the same average discharge burnup.